Management of Character Education in Realizing Cadets Who Ethically in Politeknik Pelayaran Surabaya - Putri, Indira Maharani; Roesminingsih, Erny; Wuryani, Eni (Universitas Malikussaleh, 2019)
In this time, advances in technology and science are becoming increasingly dominant in changing character or actions and public trust. The impact of many problems that occur between children and adolescents is violence and acts of anarchy, theft, no matter the rules, fighting between students, disrespect, ways of using language and speaking poorly, low morale, lack of respect for parents and teachers, low sense of individual and citizen responsibility, and lack of compassion and respect among friends (Lickona, 2016: 20). Such conditions that make educational institutions raise the question of the extent to which he manages character education in students (Novitri, 2013). This research is an interactive type of qualitative method. The main data source in this study was obtained by snowball sampling. Data collection techniques in this study used three techniques, namely observation, interviews, and documentation. Politeknik Pelayaran Surabaya is a university that has a strong commitment to organizing character education programs. The conclusion of this study states that the management of character education in Politeknik Pelayaran Surabaya has been done well and effectively.